EFFECTS OF COGNITIVE READING STRATEGY TRAINING ON READING PERFORMANCE OF EFL STUDENTS: A CASE OF A HIGH SCHOOL IN VIETNAM - Lạc, Minh Thư (Trường Đại học Đà Lạt, 2023)
Reading can be seen as an essential skill that language learners need to be good at, for it is one of the means of transferring many pieces of valuable knowledge in many fields of the world to many people and nations. One of the common barriers for many Vietnamese students studying English as a Foreign Language to acquiring reading skills is reading anxiety. For years, various researches have been conducted to test the effectiveness of students' using cognitive reading strategies and of teachers’ reading strategy instruction to improve students’ performance in class. The present study aims to find out the effects of cognitive reading strategy training on Vietnamese EFL students’ reading performance in an upper secondary school in Vinh Long province, Vietnam. Furthermore, this study aims to find out students’ perceptions on the effectiveness of the training session in their use of cognitive reading strategies. The two groups, including 32 students in the experimental group and 37 students in the control group, participated in the study. The study utilized a mixed-method approach in which both qualitative and quantitative data from the questionnaire and interview were collected. The results from the data indicated that via cognitive reading strategy instruction, EFL students in the educational setting achieved a significant improvement in reading comprehension and they also had positive perceptions on the necessity of cognitive reading strategy training.